2017
DOI: 10.3847/1538-4357/aa8b14
|View full text |Cite
|
Sign up to set email alerts
|

Planetary Ices and the Linear Mixing Approximation

Abstract: The validity of the widely used linear mixing approximation for the equations of state (EOS) of planetary ices is investigated at pressure-temperature conditions typical for the interior of Uranus and Neptune. The basis of this study are ab initio data ranging up to 1000 GPa and 20 000 K calculated via density functional theory molecular dynamics simulations. In particular, we calculate a new EOS for methane and EOS data for the 1:1 binary mixtures of methane, ammonia, and water, as well as their 2:1:4 ternary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 64 publications
6
64
1
Order By: Relevance
“…The above expression neglects nonideal mixing contributions to h F a , but simplifies the calculations [22,23]. Nonideal mixing effects on equation of state quantities were found to be very small in calculations of waterammonia-methane mixtures under similar conditions [24]. Nevertheless, avoiding this approximation is possible, and a comparison with results from an exact expression for λ nuc was made, see the appendix.…”
Section: Theoretical Methods and Simulation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The above expression neglects nonideal mixing contributions to h F a , but simplifies the calculations [22,23]. Nonideal mixing effects on equation of state quantities were found to be very small in calculations of waterammonia-methane mixtures under similar conditions [24]. Nevertheless, avoiding this approximation is possible, and a comparison with results from an exact expression for λ nuc was made, see the appendix.…”
Section: Theoretical Methods and Simulation Proceduresmentioning
confidence: 99%
“…similar as in [22,56]. This may be required for systems where nonideal mixing effects in the thermodynamic functions are not as small as those in warm dense water and other planetary ices [24].…”
Section: A3 Comparative Validation Of Both Variants Against Each Othermentioning
confidence: 99%
“…This is certainly a simplification since the further ice-forming elements carbon, nitrogen, and sulphur are likely to be present in the interior as well. Former work has shown that the presence of ices lighter than water in solar element ratios can lead to the extreme case of an icy inner envelope (Podolak & Reynolds 1987) and hence a cooler planet (Bethkenhagen et al 2017). On the other hand, rocks may be soluble in hydrogen and thus be present to some degree in the envelope at the expense of ices, while methane may be insoluble in water and may lead to carbon sedimentation.…”
Section: Equations Of Statementioning
confidence: 99%
“…The former involves very moderate computational effort but is of limited accuracy due to the use of approximate kinetic energy and entropy functional. The latter class of DFT approaches on the other hand yields reliable and accurate results and is emerging as the method of choice in the field, with applications rangingfrom short pulse laser simulations [35,36] and xray scattering [37,38] to properties of astrophysical bodies [8,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%